Development of Sendudes Web-Based Application as a Digitalization of The Village Population Census: Study Case : Desa Kota Pari - Ahmad Akbar; Indri Sulistianingsih; Heri Kurniawan; Ririn Darma Putri (JURNAL TEKNOLOGI DAN ILMU KOMPUTER PRIMA (JUTIKOMP), 2023)
This research aims to design and develop a web-based application called Sensudes as a digital record-keeping system for the population census in Kota Pari Village, using Agile Development Methods. Sensudes is created to facilitate the recording of population census data to obtain accurate and timely results. Agile Development Methods are utilized to produce a targeted product with a short development time. This research is expected to benefit the village officials in the Kota Pari Pantai Cermin subdistrict in recording population census data in an easier and more efficient manner. The research includes user requirement analysis, system design, application development, and application testing with users. The results of this research demonstrate that the web-based Sensudes application can ease and assist village officials in recording population census data. In addition, the findings of this research can be a reference for other villages and regions that want to develop efficient and user-friendly population census applications.